2020
DOI: 10.1039/c9sc05722f
|View full text |Cite
|
Sign up to set email alerts
|

Photoexcited Pd(ii) auxiliaries enable light-induced control in C(sp3)–H bond functionalisation

Abstract: Visible light irradiation of 8-aminoquinoline Pd(ii) complexes initiates photoinduced electron transfer with alkyl halides, affording C–H halogenation over C–C bond adducts. A method for inert C(sp3)–H bond halogenation (Br, Cl and I) is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…In 2020, the Polyzos group reported a creative method for the halogenation of β-C(sp 3 )−H bonds with alkyl halides (Scheme 133). 364 By visible light excitation of the palladacycle, an electron transfer to the alkyl halide produces a palladium(III) intermediate, which can either undergo disproportionation or be oxidized by Oxone to generate a palladium(IV) complex. Reductive elimination from the palladium(IV) complex affords the halogenation product in moderate to good yields.…”
Section: 215mentioning
confidence: 99%
“…In 2020, the Polyzos group reported a creative method for the halogenation of β-C(sp 3 )−H bonds with alkyl halides (Scheme 133). 364 By visible light excitation of the palladacycle, an electron transfer to the alkyl halide produces a palladium(III) intermediate, which can either undergo disproportionation or be oxidized by Oxone to generate a palladium(IV) complex. Reductive elimination from the palladium(IV) complex affords the halogenation product in moderate to good yields.…”
Section: 215mentioning
confidence: 99%
“…As part of a program at better understanding the mechanisms of metal-catalyzed C−H functionalization reactions, we have been using mass spectrometry-based methods to either interrogate solution-phase reaction mixtures 5,6 or probe fundamental gas-phase reactivity. 7,8 Recent work has demonstrated that group 10 cationic complexes [(phen)M(R)] + can catalyze deoxygenation reactions of fatty acids 9 and the acceptorless dehydrogenation of ethane (eq 1 and Scheme 1A; M = Ni, Pd, and Pt, R = H and CH 3 CH 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…As part of a program at better understanding the mechanisms of metal-catalyzed C–H functionalization reactions, we have been using mass spectrometry-based methods to either interrogate solution-phase reaction mixtures , or probe fundamental gas-phase reactivity. , Recent work has demonstrated that group 10 cationic complexes [(phen)­M­(R)] + can catalyze deoxygenation reactions of fatty acids and the acceptorless dehydrogenation of ethane (eq and Scheme A; M = Ni, Pd, and Pt, R = H and CH 3 CH 2 ) . The fact that such complexes not only lead to cracking of the fatty acid backbone, as exemplified by the sequential reactions shown for the stearate complex (eqs and ), but can also activate the C–H bonds of ethane (eq ) suggested that they could be used as depolymerization catalysts. , …”
Section: Introductionmentioning
confidence: 99%
“…Multinuclear NMR spectroscopy showed that other coordinating solvents such as MeCN or DMSO also gave adducts tentatively assigned as 7·NCMe and 7·DMSO , but these could not be isolated as crystalline solids. Diamagnetic Pd analogues are known. As shown in Scheme a), the C–H activation of 3 liberates 1 equiv of [AQ piv ]H ( 1a ), which was observed by 1 H NMR spectroscopy. The C–H activation 5 in the absence of added base also produced 1a , presumably because the t BuCO 2 H produced by deprotonation of the C–H bond protonates unreacted 5 , generating [AQ piv ]H ( 1a ), which lowers the yield.…”
Section: Results and Discussionmentioning
confidence: 98%